2007
DOI: 10.1111/j.1600-0765.2007.00974.x
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune responses of gingival epithelial cells to nonperiodontopathic and periodontopathic bacteria

Abstract: The nonperiodontopathic, the orange-complex, and the red-complex bacteria had different effects on the innate immune responses from gingival epithelial cells, which may affect the outcome of their host-microbial interaction in gingival sulcus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
113
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(127 citation statements)
references
References 36 publications
11
113
2
1
Order By: Relevance
“…Extensive results have documented the responses of epithelial cells after challenge with planktonic oral bacteria (Huang et al, 2004;Hasegawa et al, 2007;Ji et al, 2007;Stathopoulou et al, 2010). However, current models of the host-microbe interactions in the oral cavity emphasize the critical nature of complex microbial biofilms that form unique microbial ecologies (Colombo et al, 2009;Darveau, 2009) and that change during transition from health to disease (Marsh, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Extensive results have documented the responses of epithelial cells after challenge with planktonic oral bacteria (Huang et al, 2004;Hasegawa et al, 2007;Ji et al, 2007;Stathopoulou et al, 2010). However, current models of the host-microbe interactions in the oral cavity emphasize the critical nature of complex microbial biofilms that form unique microbial ecologies (Colombo et al, 2009;Darveau, 2009) and that change during transition from health to disease (Marsh, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…While the vast majority of in vitro studies have been conducted under aerobic conditions (Hasegawa et al, 2007;Ji et al, 2007;Guggenheim et al, 2009), a recent study reported that under reduced oxygen tension (i.e., 2% oxygen), selected oral bacteria, including P. gingivalis, elicited elevated levels of cytokines/chemokines in a low oxygen environment (Grant et al, 2010). This model system will enable us to explore variations in the oxygen level, volatile sulfur compounds, and elevated pH on the host-bacterial biofilm interactions that would be expected to occur in periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations